Legal Consequences of Designating Cultivation Rights as Abandoned Land in the Context of Credit Collateral Objects - Elmadiantini Elmadiantini; Febrian Febrian; Annalisa Yahanan; Firman Muntaqo (Sriwijaya Law Review, 2025)
Land rights under the Cultivation Rights Title (HGU) can serve as collateral in credit agreements through the imposition of a mortgage right. However, legal challenges arise when the status of HGU land as collateral changes, particularly due to its designation as abandoned land by the Indonesian Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). Such status changes have significant legal implications for credit agreements, mortgage rights, and the economic value of collateralized land. This study analyses the legal framework governing the determination of abandoned land status, examining statutory regulations and their impact on credit agreements and collateral objects. Employing a normative legal research methodology, the study utilises statutory analysis, conceptual exploration, and interpretative approaches to assess the legal consequences of such status changes. The findings reveal that the designation of land as abandoned results in the termination of cultivation rights and the extinguishment of mortgage rights. While the credit agreement itself remains legally binding, the loss of economic value in the collateral renders it non-executable, leading to financial losses for both creditors and debtors. To address these legal uncertainties, the study recommends amendments to the regulatory framework governing abandoned land to enhance legal certainty, ensure fairness, and provide adequate protection for both creditors and debtors.